Profil Kandungan Total Fenol, Flavonoid serta Antioksidan pada Buah Golden Berry (Physalis peruviana) Kamojang Jawa Barat - Paula Krisanty; Dewi Inderiaty; Purnama Fajri (Jurnal Kesehatan Indonesia, 2023)
The adequate nutrition helps reduce the rate of immune suppression in HIV-infected individuals and promotes adherence to treatment. In contrast, inadequate nutrition and food insecurity tend to accelerate disease progression and are associated with poorer treatment outcomes for PLHIV. These conditions have occurred, associated with lower CD4 counts and decreased immunity, increased risk of transmission and metabolic syndrome, increased risk of infection, increased risk of death, poor adherence to HAART and reduced quality of life. Golden berry is scientifically known as Physalis peruviana. This fruit is the size of a marble and is yellowish in color in Indonesia, this fruit is known as Ciplukan. This study used an extract trial using complete randomized design. The test was carried out at the Spice and Medicinal Plants Laboratory, Bogor, West Java. The results showed that the Kamojang Golden Berries (GBK) grown at Daniel's Farm, Mount Kamojang, West Java, were proven to contain an antioxidant content of 376,17 ppm and antioxidant compounds: Flavonoids of 1.30 mg/100 g; Carotenoids of 8.48 ppm, means that GBK fruit has antiviral, anti-inflammatory and anticancer effects; and Phenol of 44.46 mg GAE/100 g, meaning that GBK fruit acts as an anti-aging and free radical scavenger. GBK fruit extract can be used as an alternative therapy in overcoming the problem of decreased immune system, especially CD4 count which often occurs in HIV/AIDS patients.